The significance of the nursing actions in psychiatric hospitalization of female adolescent users of psychoactive substances - Rita Mello de Mello; Jacó Fernando Schneider; Cíntia Nasi; Marcio Wagner Camatta; Eglê Rejane Kohlrausch; Annie Jeanninne Bisso Lacchini; Tainá Moreira de Mello (Universidade Federal do Rio Grande do Sul, 2021)
ABSTRACT Objective To understand the significance of the actions developed by the nursing team in a Psychiatric Inpatient Unit for adolescent female users of psychoactive substances in the light of Alfred Schutz's phenomenological sociology framework. Method Qualitative study with Alfred Schutz's Phenomenological Sociology approach. Four nurses and 17 nursing assistants and technicians from a General Hospital in the city of Porto Alegre participated in the study. Results Three concrete categories emerged: nursing actions as being-with-the-other; collective nursing actions as a potential for shared act and nursing actions as expectations and challenges. Final considerations The actions developed by the nursing team are established through intersubjective relationships, based on bonding and dialogue, but there is still a need for nursing to enhance its actions by expanding the offer of collective therapeutic activities aligned with the psychosocial care model.